Influência da luz pulsada sobre a histologia, metabolismo de vitamina C e compostos fenólicos no armazenamento de acerolas - Sanches, Alex Guimarães (2018)
Acerola is a tropical fruit recognized for its high content of bioactive compounds with emphasis on vitamin C and phenolic compounds, however, high perishability after harvesting requires conservation techniques that allow the increase or maintenance of these compounds during the period of storage. In this context, pulsed light (PL) presents as a postharvest technology used as an abiotic stressor capable of preserving / increasing the nutritional quality of fruits and vegetables through the increase of phytochemicals. Thus, the present study aimed to investigate the effects of post-harvest application of PL (0.6 J.cm-2) on the structure and physiology of 'Okinawa' acerola during refrigerated storage (10 °C). A completely randomized experimental design was used under a 2x5 factorial arrangement, corresponding to two treatments: (with PL and without PL) and five storage times (0, 1, 4, 10 and 16 days), with three replications, and the experimental plot composed of trays containing 200 g of fruit. Each storage period was evaluated: total vitamin C content, reduced (AsA) and oxidized (DHA), the enzymatic activity of L-galactone-1,4-lactone dehydrogenase (GalLDH), ascorbate oxidase (AO), ascorbate peroxidase (APX), monodehydroascorbate reductase (MDHAR), dehydroascorbate reductase (DHAR) and glutathione reductase (GR). The content of total phenolic compounds, yellow flavonoids, monomeric anthocyanins, phenylalanine ammonia lyase (PAL), polyphenoloxidase (PPO) activity and microscopic analysis to assess the influence of treatment on tissue histology were also investigated. In general, PL treatment reduced the level of ascorbic acid oxidation through reduced ascorbate oxidase (AO) activity and stimulated the performance of the recycling enzymes (MDHAR and DHAR) resulting in a higher concentration of total vitamin C and of AsA reduced at the end of 16 days. The content of yellow flavonoids and monomeric anthocyanins did not differ (p>0.05) between treatments, however, total phenolic compounds were significantly preserved in PL treated fruits because of a higher activity of PAL and inhibition of oxidative activity of PPO. The histological study showed that PL preserved the integrity of the epicarp and mesocarp cells of the fruits with storage time. These results suggest that PL (0.6 J.cm-2) can be used as a postharvest treatment to preserve the content of vitamin C and phenolic compounds through changes in the metabolism of synthesis and degradation of these compounds.